Pengaruh Model Kooperatif Tipe TGT Terhadap Hasil Belajar Siswa Di UPT SD Negeri 174 Gresik - Cahyani, Elza Regita; Fadlillah, M. (JOURNAL OF EDUCATION FOR ALL, 2024)
This research aims to determine whether or not there is an influence of using the Teams Games Tournament (TGT) type cooperative model on student learning outcomes in theme 8 Subtheme 3 class V UPT SD Negeri 174 Gresik. The research method used was quantitative with a pre-experimental research design in the form of one group pretest-posttest. The sample in this research was 22 class V students. The data collection techniques used are tests and observations. Based on the results of the hypothesis test which was carried out using the paired sample t-test, it shows that the 16,850 > 2,086. Based on the testing criteria, if > , then is rejected and is accepted. Similar results were also obtained from the significance value obtained, namely 0,000 < 0,05, which means that was rejected, so it can be concluded that there is a significant difference between before and after the implementation of the Teams Games Tournament (TGT) type cooperative learning model. This significant difference proves that there is an influence of the Teams Games Tournament (TGT) type cooperative learning model on student learning outcomes at UPT SD Negeri 174 Gresik.